The effects of copper, calcium, and nickel on the olfactory response of fathead minnows: from neurophysiology to behaviour - Dew, William A. (My University, 2014)
The olfactory system is essential for a fish to be successful in an ecological context, and has been demonstrated to be sensitive to a variety of toxicants. The current biotic ligand model (BLM) for copper is an acute-toxicity model based on the gill that is used to predict site-specific safe copper concentrations. Recently, work has been done to develop a BLM based on a more sensitive tissue, namely the olfactory epithelium. The work presented in this dissertation determines that a number of the assumptions of the current acute-toxicity gill-based BLM do not hold for the olfactory epithelium. Two techniques were employed for the work contained within this dissertation, a neurophysiological measure of olfactory acuity, electro-olfactography (EOG), and measurement of behavioural responses. For all experiments, fathead minnows (Pimephales promelas) and yellow perch (Perca flavescens) were used as these species are ubiquitous in waterways across Canada. Fathead minnows were exposed to low, ecologically-relevant concentrations of copper for varying exposure durations in hard and soft water. While it was determined that there was a significant of inhibition of olfactory function as measured by EOG, there was recovery, at least partially, of EOG function with increased exposure duration. It was also determined that not only does calcium have no protective effect against copper-induced olfactory dysfunction at the olfactory epithelium as it does at the gill, but calcium induces its own response. The response to calcium in fathead minnows was further investigated. Fathead minnows had a strong olfactory-dependent avoidance response to calcium. The reduction in EOG response caused by calcium was demonstrated to be due to cross-adaptation with the odourant used, namely L-arginine. Different olfactory sensory neuron (OSN) classes within the olfactory epithelium respond specifically to different odourants. Exposures of fathead minnows or yellow perch to copper demonstrated that there was a specific impairment of ciliated OSNs, while exposure to nickel resulted in impairment of microvillous OSNs. Behavioural work with fathead minnows using an anti-predator cue demonstrated that copper impairs the response to an anti-predator cue, while nickel does not. These observations demonstrate that ciliated cells are responsible for mediating response to anti-predator cue, which is the first time response to a specific chemosensory cue has been directly connected with a specific OSN class. The work presented in this dissertation represents a significant advancement in our understanding in how copper impairs the olfactory system of fish, which will aid in the construction of models and regulations to protect fish populations.
Keywords: Olfactory system; Biotic ligand model (BLM); Olfactory epithelium; Measuring olfaction; Olfaction impairment